Fault Tolerant Control for descriptor systems using the concept of virtual actuator and virtual sensor - Deng, Hao; Chadli, Mohammed; Stoica, Cristina (International Conference on System Theory, Control and Computing, 2024)
This paper proposes a fault tolerant control strategy for discrete-time descriptor systems using a reconfiguration-based technique. The proposed approach is designed to achieve fault-tolerance capabilities without modifying the nominal controller of the descriptor system but adding a reconfiguration block including a virtual sensor and a virtual actuator. The implementation of the virtual actuator and virtual sensor is based on the system input-to-state stability criterion through linear matrix inequalities. Finally, the effectiveness of the proposed technique is illustrated on an academic simulation example.